2018
DOI: 10.1053/j.gastro.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Advanced, Precancerous Colorectal Neoplasms in Black and White Populations: A Systematic Review and Meta-analysis

Abstract: In this meta-analysis, we found the overall prevalence of AA and ACN did not differ significantly between average-risk black and white persons, indicating that the age at which to begin colorectal cancer screening need not differ based on race alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…No conclusive evidence exists for any sort of racial/ethnic biological or genetic determinant of CRC outcomes. [39][40][41][42] On the other hand, cultural and personal beliefs, though difficult to measure, may substantially impact health outcomes. Indeed, studies have shown that even when rates of specialist consultations are similar between Black and…”
Section: Disparities In Treatment Receipt and Relative Cost Ratiosmentioning
confidence: 99%
“…No conclusive evidence exists for any sort of racial/ethnic biological or genetic determinant of CRC outcomes. [39][40][41][42] On the other hand, cultural and personal beliefs, though difficult to measure, may substantially impact health outcomes. Indeed, studies have shown that even when rates of specialist consultations are similar between Black and…”
Section: Disparities In Treatment Receipt and Relative Cost Ratiosmentioning
confidence: 99%
“…CRC has many causes, and it is generally believed that genetics, age, environment, lifestyle, and other factors affect its occurrence CRC [6–8]. Among these other factors, dietary patterns have received the most recent attention [912].…”
Section: Introductionmentioning
confidence: 99%
“…38 A prior study demonstrated no difference in advanced precancerous colorectal neoplasms (largely comprised of advanced polyps, precursor lesions for most CRCs) between Blacks and Whites undergoing average-risk colonoscopy. 39 The authors concluded differences in CRC incidence are less likely due to biology and more likely due to behavioral or sociocultural differences in symptom recognition, need for diagnostic evaluation and/or access or uptake of preventive services and the age to initiate screening need not vary based on race alone. Given marked geographic and intra-racial EOCRC rate disparities we have identified within both White and Black populations at very young ages (i.e., [30][31][32][33][34][35][36][37][38][39], prior to screening age) argues other factors in addition to symptom recognition or screening access may underlie such variations.…”
Section: Discussionmentioning
confidence: 99%